Recent progress in the applications of boron doped diamond electrodes in electroanalysis of organic compounds and biomolecules - A review - Baluchová, Simona; Daňhel, Aleš; Dejmková, Hana; Ostatná, Veronika; Fojta, Miroslav; Schwarzová-Pecková, Karolina (Analytica chimica acta, 2019)
This review summarizes progress in electroanalysis of organic compounds and biomacromolecules by means of bare BDD-based electrodes for the period of 2009-2018. New trends, which have emerged in the reported decade and which have improved their performance in batch voltammetric and amperometric methods and electrochemical detection in liquid flow techniques are commented. Importance of BDD surface termination, effect of boron doping level, and utilization of adsorption of analytes on BDD surfaces enabling development of adsorptive voltammetric techniques are addressed. Further, possibilities of simultaneous determination of analytes by means of voltammetric techniques utilizing computational approaches and multiple-pulse amperometric detection are discussed. Strategies leading to enhancement of sensitivity such as nanostructuring of the BDD surface, fabrication of BDD-based composite materials or new approaches in construction of microelectrodes and microelectrode arrays for biosensing represent another area of interest. Attention is paid to possibilities in detection of amino acids, peptides and proteins, nucleobases, nucleos(t)ides and DNA/RNA.
Keywords: Organic Chemicals; Electrochemical Techniques; diamant; Non-enzymatic electroanalysis; Boron; DNA; Surface treatment; RNA; Diamond; Biomolecules; Proteins; peptidy; proteiny; Boron doped diamond; Organic compounds; elektrochemické techniky; organické látky; Microelectrodes; mikroelektrody; bor; Peptides